The Feasibility Study of The Drinking Water Supply at Grand Dharmahusada Lagoon Apartement of Surabaya - Mardiyanti Adnan Aksa; Wahyono Hadi (Jurnal Teknik ITS, 2019)
The city of Surabaya has become the most targeted city for developers to set up apartments. Many residents outside Surabaya want to live in Surabaya because of their work or business. No wonder the number of water needs in Surabaya is increasing. The Grand Dharmahusada Lagoon apartment is the location to be studied for the feasibility of developing a ready-to-drink system There are three alternatives offered to provide ar ready to drink, namely (1). Everything that comes out of the apartment faucet is ready to drink water; (2) ready-to-drink water only in kitchen units of apartment units; and (3) ready-to-drink water is provided by the apartment for each unit in the form of Gallon packaging. From the results of a comparison of the water quality test of PDAM Kota Surabaya with the quality standards of bottled drinking water, several parameters were obtained which still exceeded the applicable quality standards. The technology used to treat PDAM water into ready-to-drink water is to use Ultrafiltration, Carbon Filter and Ozone